The complete mitochondrial genome of Ormosia boluoensis - Wang, Zheng-Feng; Zhang, Yue; Zhong, Xiang-Jing; Kang, Ning; Cao, Hong-Lin (Mitochondrial DNA. Part B. Resources, 2021)
Ormosia is a particular genus in the Fabaceae family with its striking seeds. The genus Ormosia boluoensis is a newly reported and critically endangered species, and field investigations have indicated that there are only hundreds of it. For the effective conservation, we report its complete mitochondrial genome. The length of the O. boluoensis mitochondrial genome is 248,619 bp, including 28 protein-coding genes, 14 transfer RNA genes, 3 ribosomal RNA genes, and 45 simple sequence repeats. Phylogenetic analysis revealed that O. boluoensis was a sister to the clade including Sophora flavescens, Ammopiptanthus nanus, and Ammopiptanthus mongolicus.